광학 우주 관측 시스템의 미지 우주물체 위치 추적 분석 - 현철(Chul Hyun); 이상욱(Sangwook Lee); 이호진(Hojin Lee); 박승욱(Seung-Wook Park) (한국정보통신학회논문지, 2021)
In this paper, we check the possibility of continuous tracking when photographing unknown space objects in a short period of time in an optical observation system on the ground. Simulated observation data were generated for target limited to low-orbit areas. The performance index of the prediction error was set in consideration of the property of targets. Kalman Filter was applied to predict the next location of the target. A constant velocity/acceleration dynamic model was applied to the two axes of the azimuth/elevation of the unknown space object respectively. As a result of performing the Monte Carlo simulation, the maximum error ratio of the maximum nonlinear section was less than 2%, which could be determined to ensure continuous tracking. The CA model had little change in the prediction error value for each case, making it more suitable for tracking unknown space objects. This analysis could provide a foundation for determining the orbit of unknown space objects using optical observation. 본 논문에서는 지상의 광학 관측 시스템에서 미지 우주물체를 짧은 주기로 촬영할 때의 연속 추적 가능성을 확인해 본다. 저궤도영역으로 한정된 대상 표적에 대해 모의 관측 데이터를 생성하였고, 표적특성을 고려하여 예측 오차의 성능지수를 설정하였다. 칼만 필터를 이용하여 표적의 다음 위치를 예측하였고, 등속도/등가속도 표적 기동 모델이 미지 우주물체의 방위각/고도각 두 축에 적용되었다. 몬테카를로 시뮬레이션을 수행한 결과, 최대 비선형구간의 최대 오차 비율이 2% 미만으로 나타나 연속적인 추적을 보장할 수 있다고 판단할 수 있었다. 등가속도 모델이 케이스별 예측 오차값의 변화가 적어서, 미지 우주물체의 추적에 더 적합하였다. 이러한 분석은 광학 관측을 이용한 미지 우주물체 궤도 결정의 기초를 제공할 수 있다.